An Islamic perspective on the true and fair view override principle - Salihin, Abang; Abdul Hamid, Fatima; Abdulrahman Anam, Ousama (Emerald Group Publishing Limited, 2014)
Purpose – This paper aims to determine whether the “true and fair view override” (TFVO) principle is relevant and applicable in Islamic accounting. In addition, the paper examines the roles that TFVO could play in Islamic accounting and auditing. Design/methodology/approach – A qualitative research method was used based on documentary and textual analysis of the Shari’ah fundamentals (Islamic legal sources) and relevant accounting standards and regulations. Findings – The paper found that the TFVO is relevant and applicable in Islamic accounting and auditing and not contradictory to the rules of the Shari’ah. Therefore, the concept is acceptable for use in Islamic accounting. Moreover, based on the several roles played by the TFVO, in the Islamic context, the practicality of this concept in Islamic accounting provides further justification for its continued usage. Practical implications – The findings of the paper provide a basis to support the inclusion of theTFVO in Islamic accounting standards, as well as possible usage by Islamic financial institutions (IFIs). Thus, regulators of IFIs and Islamic accounting standards setting bodies can consider it in their challenging task of standardizing accounting practices due to the different interpretations of transactions from the various Madhahib and multiple accounting concepts and practices. In addition, the discussion in the paper reminds accountants and auditors of IFIs and Islamic organizations that providing a true and fair view (TFV) is paramount; thus an override of inapplicable accounting standards and regulation is allowed, but not Shari’ah. Thus, TFVO can assist accountants to record transactions that reflect the economic reality of the IFIs, especially prior to accounting regulations keeping pace with the rapid business environment. Originality/value – The paper has highlighted a very important issue relating to the TFV, specifically the TFVO, from the Islamic perspective. The paper is considered as the first paper that contextually analyses this issue based on Islamic legal sources using a qualitative approach. In addition, the paper has contributed to the literature in Islamic accounting and auditing.